The runaway greenhouse on sub-Neptune waterworlds - Pierrehumbert, RT (American Astronomical Society, 2023)
The implications of the water vapor runaway greenhouse phenomenon for water-rich sub-Neptunes are developed. In particular, the nature of the postrunaway equilibration process for planets that have an extremely high water inventory is addressed. Crossing the threshold from subrunaway to superrunaway conditions leads to a transition from equilibrated states with cold, deep liquid oceans and deep interior ice-X phases to states with hot supercritical fluid interiors. There is a corresponding marked inflation of radius for a given mass, similar to the runaway greenhouse radius inflation effect noted earlier for terrestrial planets, but in the present case the inflation involves the entire interior of the planet. The calculation employs the AQUA equation-of-state database to simplify the internal structure calculation. Some speculations concerning the effect of H2 admixture, silicate cores, and hot- versus cold-start evolution trajectories are offered. Observational implications are discussed though the search for the mass–radius signature of the phenomena considered is limited by degeneracies and by lack of data.